Characterization of Ni0.5LiXZn(0.5-X)Fe2O4 synthesized by co-precipitation method - Rohadiana Dwi Nofianti; Zul Azhar, Zahid Jamal; Md Fazlul, Bari; Shamsul Baharin, Jamaludin, Prof. Dr. (SIRIM, 2011)
4th Malaysian Powder Metallurgy Symposium (MPMS) and Malaysian Metallurgical Conference (MMC) 2010 organized by SIRIM Berhad on 22nd - 23rd November 2010 at Parkroyal Hotel, Penang, Malaysia.